2013
DOI: 10.5430/jnep.v3n12p70
|View full text |Cite
|
Sign up to set email alerts
|

TIGER-based measurement of nursing informatics competencies: The development and implementation of an online tool for self-assessment

Abstract: Background/Objective: The aim of this research was to develop a reliable, valid instrument for self-assessment of perceived nursing informatics (NI) competencies. This article describes the development and validity assessment of the instrument.Informatics competencies are deemed a necessity in today's technologically-rich healthcare delivery system. Work to identify essential informatics skills commenced shortly after the introduction of information technology into healthcare. In subsequent years, professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 10 publications
0
32
1
2
Order By: Relevance
“…18 Nursing ICs, the competencies necessary for nursing informatics practice, can therefore be defined as the knowledge, skills, and attitudes to integrate nursing science, computer, and information science to Identify, collect, process, manage, communicate, and expand data, information, knowledge, and wisdom in nursing practice. 29 However, across the myriad efforts, the majority of past private and public organizations concentrated on developing and evaluating ICs for entry-level undergraduate nurses [30][31][32][33][34][35] or graduate nurses' education. 13,23,28 Public organizations including the American Nurses Association, the American Medical Informatics Association, Healthcare Information Management and Systems Society (HIMSS), the National League for Nursing, the American Association of Colleges of Nursing, and the Technology Informatics Guiding Educational Reform (TIGER) Initiative have put efforts to identify core ICs for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…18 Nursing ICs, the competencies necessary for nursing informatics practice, can therefore be defined as the knowledge, skills, and attitudes to integrate nursing science, computer, and information science to Identify, collect, process, manage, communicate, and expand data, information, knowledge, and wisdom in nursing practice. 29 However, across the myriad efforts, the majority of past private and public organizations concentrated on developing and evaluating ICs for entry-level undergraduate nurses [30][31][32][33][34][35] or graduate nurses' education. 13,23,28 Public organizations including the American Nurses Association, the American Medical Informatics Association, Healthcare Information Management and Systems Society (HIMSS), the National League for Nursing, the American Association of Colleges of Nursing, and the Technology Informatics Guiding Educational Reform (TIGER) Initiative have put efforts to identify core ICs for nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Hunter, McGonigle, and Hebda conducted a study to gain a clearer understanding of the integration of informatics content into BSN and graduate nursing education by accessing a published list of nursing schools in 2012 throughout the United States and identified as the top online schools by the U.S. News & World Report [19]. Twenty-four schools were identified and reviewed.…”
Section: Review Of Literaturementioning
confidence: 99%
“…McKee [9] noted that competency is the "ability to integrate knowledge and skill to perform a task under the varied circumstances of the real world" (slide 5). Lastly, Hunter, McGonigle, and Hebda [5] concluded that Competency, then, is a concept applicable to multiple situations. At its most basic, competency denotes having the knowledge, skills, and ability to perform or do a specific task, act, or job.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many nurses are not fully prepared to adequately use health information technology (HIT) as it is intended to support patient care. A recent study by Hunter, McGonigle, and Hebda [5] of nursing-school course offerings showed an absence of clear delineation of nursing informatics content across graduate curricula. As the demand for informatics competencies in nursing increases, nurse educators must be able to prepare not only nurses as basic users of HIT but also informatics nurse specialists (INSs) as innovators and leaders in the evolution of NI.…”
Section: Introductionmentioning
confidence: 99%